Overweight in epilepsy as a risk factor for pregnancy and delivery complications. (13th October 2016) - Kolstad, Eivind; Veiby, Gyri; Gilhus, Nils Erik; Bjørk, Marte
Summary: Objective: To investigate whether prepregnancy overweight in women with epilepsy increases their risk for complications during pregnancy and delivery. Methods: This study is based on The Norwegian Mother and Child Cohort Study (MoBa) linked to the Medical Birth Registry of Norway. A diagnosis of epilepsy was reported in 706 pregnancies. Overweight was defined as body mass index ≥ 25 prepregnancy. Overweight women with epilepsy (n = 259) were compared to normal‐weight women with epilepsy (n = 416), and to women without epilepsy with and without overweight (n = 30, 516 and n = 67, 977, respectively). The risks of pregnancy and delivery complications were calculated as odds ratios (ORs) with 95% confidence intervals (CIs) adjusted for adverse socioeconomic factors, age, parity, and smoking. Results: Women with epilepsy were more often overweight than women without epilepsy (38.4% vs. 31.3%, p < 0.001). The majority of pregnancy and delivery complications were more frequent in overweight women with epilepsy. Compared to overweight women without epilepsy, the risk was increased for cesarean section (OR 1.6, CI 1.2–2.2, p < 0.001), excessive bleeding (OR 1.4, CI 1.0–1.8, p = 0.04), peripartum anxiety and depressive symptoms (OR 1.9, CI 1.3–2.8, p < 0.001), small for gestational age children (OR 2.4, CI 1.2–4.8, p = 0.02), and transfer of the infant to a neonatal ward (OR 1.5, CI 1.1–2.2, p = 0.02). Compared to normal‐weight women with epilepsy, the risk of cesarean section (OR 1.6, CI 1.1–2.3, p < 0.05), gestational hypertension (OR 2.0, CI 1.1–3.5, p < 0.05), preeclampsia (OR 2.3, CI 1.2–4.5, p < 0.05), and transfer of the infant to a neonatal ward (OR 2.2, CI 1.3–3.6, p < 0.01) was increased. Significance: Prepregnancy overweight in combination with epilepsy entails a strong negative effect on risk of complications during pregnancy and delivery. In women with epilepsy and overweight referral to a nutritionist should be considered when an antiepileptic drug is started as well as when pregnancy is planned. These women should be regarded as a high‐risk group.